2017
DOI: 10.1111/ina.12429
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and cognitive effects of laser printer emissions: A controlled exposure study

Abstract: The possible impact of ultrafine particles from laser printers on human health is controversially discussed although there are persons reporting substantial symptoms in relation to these emissions. A randomized, single-blinded, cross-over experimental design with two exposure conditions (high-level and low-level exposure) was conducted with 23 healthy subjects, 14 subjects with mild asthma, and 15 persons reporting symptoms associated with laser printer emissions. To separate physiological and psychological ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…While the technical quality of the measurement data from the cited work is beyond dispute, it has to be kept in mind that experimental findings from cell culture and animal studies can often not be directly transferred to real‐world settings and carefully controlled human studies in realistic exposure settings are much needed. Currently, the controlled human exposure study reported in Karrasch et al and Herbig et al represents the most comprehensive and diligent investigation of short‐term health effects of LPD‐emitted particles to date. Despite a high particle concentration throughout an exposure period of more than one hour, the observed reactions were slight to very slight and could not be convincingly classified as clinically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the technical quality of the measurement data from the cited work is beyond dispute, it has to be kept in mind that experimental findings from cell culture and animal studies can often not be directly transferred to real‐world settings and carefully controlled human studies in realistic exposure settings are much needed. Currently, the controlled human exposure study reported in Karrasch et al and Herbig et al represents the most comprehensive and diligent investigation of short‐term health effects of LPD‐emitted particles to date. Despite a high particle concentration throughout an exposure period of more than one hour, the observed reactions were slight to very slight and could not be convincingly classified as clinically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The studies discussed so far are in categories (a) to (c). The results of a human study under controlled conditions were first published by Karrasch et al and Herbig et al A total of 52 persons were each exposed to emissions from laser printers in a test chamber for 75 minutes. Twenty‐three persons were healthy, 15 persons (affected) had reported symptoms related to printer emissions prior to the studies, and 14 persons were patients with mild asthma.…”
Section: Health Effects Of Particles From Laser Printingmentioning
confidence: 99%
“…The study took place in an exposure chamber of volume 32 m 3 that is in use for occupational and environmental exposures . The air conditioning system was turned off during exposures in order to avoid a clearance of particles and to ensure a realistic setting, as most 3D printers are operated at home without ventilation, because of unwanted warping of the printed object if exposed to a temperature gradient.…”
Section: Methodsmentioning
confidence: 99%
“…[5][6][7] For laser printer devices, potential health risks from UFP have already been extensively discussed, and the available studies are ranging from cell culture experiments 8,9 to human exposures. 10,11 The UFP produced by 3D printers are also generated from volatile organic compounds (VOCs) as primary emissions of these printers, 6,7,[12][13][14][15] but with large differences between the types of plastic filaments used. [15][16][17][18] Therefore, in principle 3D printers also could pose a health risk, especially if they are used for personal purposes in the absence of professional protection measures.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation